2015
DOI: 10.1111/let.12088
|View full text |Cite
|
Sign up to set email alerts
|

First record of Otozoum from Namibia

Abstract: The first incontrovertible Otozoum moodii of Gondwana is described from the Etjo Formation (Waterberg Plateau, Namibia). Distinct Otozoum trackways and isolated footprints are reported from the Omuramba Omambonde tracksite, in the Otjozondjupa Region (North–central Namibia). Previously known only from North America, Europe and possibly Lesotho, the occurrence of Otozoum is a definitive time constraint for an Early Jurassic age of the Etjo Formation. The presence of Otozoum in the hyperarid facies and specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…förster et al 1999) in the Middle Unit of the Etjo, and the identification of a trackway referred to Otozoum moodii at the Omuramba Omambonde locality, northeast of the Waterberg Plateau (D'orazi PorcHetti et al 2015), have consistently constrained the age of this Formation to the Early Jurassic.…”
Section: Geological Settingmentioning
confidence: 96%
See 2 more Smart Citations
“…förster et al 1999) in the Middle Unit of the Etjo, and the identification of a trackway referred to Otozoum moodii at the Omuramba Omambonde locality, northeast of the Waterberg Plateau (D'orazi PorcHetti et al 2015), have consistently constrained the age of this Formation to the Early Jurassic.…”
Section: Geological Settingmentioning
confidence: 96%
“…While the remaining two forms appear to be genuinely African, one of them (Kayentapus damarensis) is similar enough to North American forms to warrant inclusion in the same ichnogenus. In addition to the rich record at Otjihaenamaparero, D'orazi PorcHetti et al (2015) recently reported Otozoum moodii trackways from the Etjo Formation at the Omuramba Omambonde tracksite, some 185 km NE of Otjihaenamaparero, adding another classical North American ichnotaxon to the Namibian Early Jurassic ichnofauna. The same ichnotaxon has recently been reported also from Northern Africa (masrour & Pérez-lorente 2014).…”
Section: Biogeographic Affinity Of the Etjo Formation Ichnofaunamentioning
confidence: 97%
See 1 more Smart Citation